Parametric Design & Analysis of Plastics Fuel Blend by using Taguchi Method in Diesel Engine - Rishabha Saraf (International Journal of Engineering and Management Research, 2021)
Over the past two centuries, energy needs have risen dramatically, particularly due to the transportation and industry sectors. However, the main made fuels like (fossil fuels) are polluting and their reserves are limited. Governments & research organization work together for make the use of renewable resources a priority and reduce irresponsible use of natural supplies through increased conservation. The energy crisis is a broad is biggest problem in world. Most people don't realize to their reality unless the price of fuel at the pump goes up or there are lines at the fuel station. Plastics waste fuel is sustainable and futuristic solution of fossil fuel as well as biggest problem of waste management of plastic waste can solve by this fuel. In thesis we prepare the plastic waste fuel by application of paralysis process in this process use low, medium and high grade of plastic and heated with limited amount of oxygen melt the plastic. The result of paralysis finds of liquid fuel and flammable gas. This fuel can be used as a blend in diesel with a proportion of B0D100, B10D90 B20D80, & B30D70 where B tent to blend of plastic fuel and D tend to diesel as if B0D100 means blend 0% and diesel 100%. These blend run diesel engine. The blends are in 10%, 20% & 30% plastic paralysis oil with standard diesel fuel. For experiment simultaneous optimization used a method called “Taguchi” used in the engine such as injection pressure and load condition. Taguchi Method of Optimization is a simplest method of optimizing experimental parameters in less number of trials.